Chatbot Menggunakan Natural Language Processing untuk Pembelajaran Bahasa Inggris Berbasis Android - Yuthsi Aprilinda; Tifanny Martavia; Erlangga Erlangga; Freddy Nur Afandi; Usman Rizal (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
Learning languages nowadays is massive and varies, therefore the interest in learning keeps increasing. But there are some limitations that cause students not to try to learn something, such as the matter of time and the fear of pronouncing and speaking a foreign language whether to people they know or do not know. Therefore, this smart English language learning application is one of the solutions as a platform for learning and practice. This application uses a Natural Language Processing (NLP) method that can act as a friend to practice speaking, especially English. This research is an option for learning languages that is more interactive and fun.